2011
DOI: 10.1007/s00204-011-0752-8
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic potency of perfluorooctane sulfonate (PFOS) on Syrian hamster embryo (SHE) cells

Abstract: Perfluorooctane sulfonate (PFOS) is the degradation product of many fluoroderivatives and a widespread environmental contaminant. Its persistence, its long half-life in humans and its toxicity explain high concerns on human health side effects in future. PFOS is suspected to be a non-genotoxic carcinogen. In the present work, we assessed carcinogenic potential of PFOS by studying morphological transformation in Syrian hamster embryo (SHE) cells; cell transformation of SHE cells is an in vitro assay recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
2
14
1
4
Order By: Relevance
“…Therefore, in the current study we attempted to investigate the consequences of a possible imbalance in the expression of PPARs caused by PFOS during early development. Interestingly, in contrast to previous in vitro studies showing activation of PPARα in kidney Cos-1 cells (Shipley et al, 2004) or PPARβ/δ in Syrian hamster embryo cells after exposure to PFOS (Jacquet et al, 2011), we found no changes in the expression of these two receptor isoforms. Instead, we detected a significant upregulation of PPARγ mRNA after exposure to 50 nM PFOS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the current study we attempted to investigate the consequences of a possible imbalance in the expression of PPARs caused by PFOS during early development. Interestingly, in contrast to previous in vitro studies showing activation of PPARα in kidney Cos-1 cells (Shipley et al, 2004) or PPARβ/δ in Syrian hamster embryo cells after exposure to PFOS (Jacquet et al, 2011), we found no changes in the expression of these two receptor isoforms. Instead, we detected a significant upregulation of PPARγ mRNA after exposure to 50 nM PFOS.…”
Section: Discussioncontrasting
confidence: 99%
“…Slotkin et al (2008) reported that PFOS influences differentiation of PC12 cells. Exposure of Syrian hamster embryo cells revealed the transforming potential of PFOS in parallel with an increased expression of peroxisome proliferator-activated receptor (PPAR) genes (Jacquet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…No genotoxicity in SHE cells was seen via the COMET assay, nor was DNA breakage increased in benzo-α-pyrene initiated cells. The data reported herein and that reported by Jacquet et al [38] demonstrate a lack of cell transformation potential in vitro to be associated with PFOA.…”
Section: Discussionsupporting
confidence: 73%
“…PFOS increased mutation frequencies at redBA/gam gene loci in gpt delta transgenic mouse embryonic fibroblasts (Wang et al., ). PFOS failed to induce DNA strand breaks in SHE cells (Jacquet et al., ) and DNA strand breaks or micronuclei in human HepG2 cells (Eriksen et al., ; Florentin et al., ). In another HepG2 study, concomitantly with increased ROS production, a non‐dose‐dependent increase in strand breaks was observed (Wielsøe et al., ).…”
Section: Assessmentmentioning
confidence: 99%